RANCANG BANGUN SISTEM INFORMASI SIMPAN PINJAM BERBASIS WEBSITE (STUDI KASUS PADA KSP SASONO MULYO MAGETAN) - Muhamad Husein Nurkholis (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
KSP Sasano Mulyo is one of the cooperatives located in Magetan. KSP Sasano Mulyo provides various services such as savings and loans to customers. The service process at KSP Sasano Mulyo is still carried out conventionally, namely recording and other services are still recorded in the book. This makes the service and presentation of information inefficient, because they have to find and open records and documents. Therefore, in this study, a website-based savings and loan information system was created. The system development method in this study uses the waterfall system development method, the PHP programming language, MySQL database and blackbox system testing. This research produces a website-based savings and loan information system. It is hoped that this information system will make it easier to access information and improve services to KSP Sasano Mulyo customers.